STRATEGI PENGUATAN PENDIDIKAN KARAKTER DAN BELA NEGARA BAGI MAHASISWA TEKNIK INFORMATIKA KELAS 2B MELALUI MODEL PEMBELAJARAN PROJECT BASED LEARNING - Ita Aristia Sa'ida (EDU RESEARCH, 2022)
The toughest challenge of education in higher education today, especially in Indonesia, is not only focusing on conventional issues of equity and fulfilment of access, infrastructure and financing of education, but also the quality of graduates who must have intellectual expertise in their fields as well as high morality and love for the country. Seeing these conditions, the availability of human resources with character and love for the country is a very important need. This is done to prepare for the global challenges and competitiveness of the nation and state today and in the future, Higher Education must be able to prepare a generation that has competence and good character (good character) and is useful for the nation and state, thus the strategy of strengthening character education and foreign affairs in learning by using the Project Based Learning learning model requires an integrated plan. The implementation of character education and Belanegara along with monitoring and evaluation must also be prepared as optimally as possible. the concept of character education and Belanegara programmatically with a good strategy such as moral knowing, moral modelling, moral feeling ang loving, moral acting, punishment, habituation. Should be applied in every university until students have an inseparable unity of good character (knowing, feeling, and acting) in everyday life.